2022
DOI: 10.3389/fnut.2022.973291
|View full text |Cite
|
Sign up to set email alerts
|

Sleep duration of lactating mothers and its relationship with feeding pattern, milk macronutrients and related serum factors: A combined longitudinal cohort and cross-sectional study

Abstract: ObjectiveInsufficient sleep is common in postpartum mothers. The main objectives of this study are to explore the sleep duration among Chinese lactating mothers and preliminarily investigate the relationship between sleep duration and feeding pattern. The secondary objectives are to investigate the relationships between sleep duration and milk macronutrients and between maternal-related indicators, including melatonin (MT), growth hormone (GH), ghrelin (GHRL), glucagon-like peptide-1 (GLP-1), prolactin (PRL), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“… 37 Breastfeeding Chinese mothers also reported about 7h00 of NSD from 2 to 7 months postpartum, and about 7h30 at 12 to 17 months. 38 Mean paternal NSD was stable, about 8 hr, from 3 to 36 months postpartum. It was also longer in our study than in other studies: the mean NSD was 6h11 at 7 weeks postpartum among US fathers 9 and about 7h20 by subjective and objective measures among Canadian fathers at 6 months postpartum.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“… 37 Breastfeeding Chinese mothers also reported about 7h00 of NSD from 2 to 7 months postpartum, and about 7h30 at 12 to 17 months. 38 Mean paternal NSD was stable, about 8 hr, from 3 to 36 months postpartum. It was also longer in our study than in other studies: the mean NSD was 6h11 at 7 weeks postpartum among US fathers 9 and about 7h20 by subjective and objective measures among Canadian fathers at 6 months postpartum.…”
Section: Discussionmentioning
confidence: 91%
“…Although most parental sleep studies measured maternal or paternal sleep by sleep diaries 19 , 36 or validated questionnaires, 9 , 10 self-reported sleep based on bedtime and wake-up time is widely used in epidemiological studies of sleep in general populations. 37 , 38 We did not collect data on the frequency and duration of parental night waking, but we considered the frequency of the child’s night waking in a sensitivity analysis showing that parental NSD was low from 3 to 18 months postpartum but remained longer than the parental sleep duration reported in other populations. 9 , 19 , 38 , 39 Another explanation for the observed long sleep durations may be the specificity of the study population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 62 Ruan et al investigated the relationship between sleep duration and breast milk macronutrient concentrations but did not find a significant correlation. 15 A study by Astbury et al has demonstrated that breastfeeding itself is not associated with lower quality and quantity of nocturnal sleep, but a higher number of nighttime feeds is a strong predictor of shorter sleep duration and poor sleep quality. 63 …”
Section: Discussionmentioning
confidence: 99%